2020
DOI: 10.1038/s41419-020-03273-4
|View full text |Cite
|
Sign up to set email alerts
|

SOX9-activated FARSA-AS1 predetermines cell growth, stemness, and metastasis in colorectal cancer through upregulating FARSA and SOX9

Abstract: SRY-box transcription factors (SOXs) are effective inducers for the formation of stem-like phenotypes. As a member of SOX family,SOX9(SRY-box transcription factor 9) has been reported to be highly expressed and exert oncogenic functions in multiple human cancers. In this study, we hypothesized thatSOX9could regulate the function of cancer stem/initiating cells (CSCs) to further facilitate the progression of colorectal cancer (CRC). Then, stable transfection of shRNAs was used to silence indicated genes. Loss-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 42 publications
2
21
1
Order By: Relevance
“…As for SOX9, it is widely known as a master regulator of cell fate through affecting multiple developmental pathways including differentiation and stemness. For example, it induced and maintained stem-like phenotypes via SOX9/LncRNA FARSA-AS1/SOX9 loop activation (27). These reports support the feasibility of our screening strategy.…”
Section: Discussionsupporting
confidence: 75%
“…As for SOX9, it is widely known as a master regulator of cell fate through affecting multiple developmental pathways including differentiation and stemness. For example, it induced and maintained stem-like phenotypes via SOX9/LncRNA FARSA-AS1/SOX9 loop activation (27). These reports support the feasibility of our screening strategy.…”
Section: Discussionsupporting
confidence: 75%
“…Zhou et al. reported that the silencing of SOX9 suppressed cell growth, stemness, migration, and invasion in colorectal cancer ( 48 ). Chen et al.…”
Section: Discussionmentioning
confidence: 99%
“…Both c-Myc and SOX9 were reported to play essential roles in normal cells and frequently dysregulated in human cancers [ 48 50 ]. For example, c-Myc and SOX9 were remarkably upregulated in the colorectal cancer and can accelerate cell proliferation [ 48 , 51 ]. In ACP primary cells, mutant β-catenin also promoted faster cell proliferation than the wild-type (Fig.…”
Section: Discussionmentioning
confidence: 99%